Paper-based multiplex surface-enhanced Raman scattering detection using polymerase chain reaction probe codification - Kang, Minhee; Kim, Eun Ju; Kim, Hanbi; Park, Eunkyoung; Kim, Taekyung; Chung, Doo Ryeon; Choi, Young Man (Analytical Chemistry, 2021)
We construct a multiplex surface-enhanced Raman scattering (SERS) platform based on a plasmonic paper substrate and a double-labeled probe for the detection of multiple fluorescent dyes at high sensitivity in a single-wavelength light source system. Plasmonic paper, made of silver nanodots on three-dimensional cellulose fibers, enables highly sensitive SERS biosensing based on localized surface plasmon resonance (LSPR). The proposed method enables the identification and quantification of a range of fluorescent dyes ranging from picomolar to millimolar concentrations. The use of 5′ fluorescent dyes and 3′ biotin-modified probes as SERS-coded probes renders possible the separation of fluorescent dyes with streptavidin-coated magnetic beads (SMBs) and the sensitive detection of multiple dyes after the reverse transcription polymerase chain reaction (RT-PCR). This experimental study reveals the multiplex detection capability of PCR-based SERS under existing PCR conditions without modifying primer and probe sequences. The combination of magnetic bead-based separation and paper SERS platform is efficient, economical, and can be used for the simultaneous detection of two or more pathogens.
Keywords: Double-labeled probes; Localized surface plasmon resonance; Millimolar concentrations; Multiplex detections; Reverse transcription-polymerase chain reaction; Simultaneous detection; Single-wavelength light; Surface enhanced Raman Scattering (SERS)